Essays in labor economics using Brazilian data - Arabage, Amanda Cappellazzo (2018)
This thesis is composed of three essays in applied microeconomics. In all essays, we investigate different aspects related to the Brazilian formal labor market using data from the Relação Anual de Informações Sociais - RAIS. In the first two chapters, we examine the impacts of two educational policies on labor market outcomes of those involved. In the third chapter, we study wage inequality in the formal labor market. We aim to contribute to the debate on inequality reduction policies by providing additional empirical evidence for Brazil. In the first chapter, we investigate the impacts of the provision of free child care for children aged 0-3 on mothers and fathers’ labor market outcomes in the formal sector of the economy. We exploit an exogenous variation introduced by the fact that, for the 2008 school year, access to public day care centers was randomly assigned in the municipality of Rio de Janeiro. Our results suggest that the provision of this service had no impacts on parents’ probabilities of being employed in the formal sector and related labor market outcomes (e.g. hours worked, wages) in the short or medium terms. We argue that high labor market participation, relatively low flexibility of the formal labor market and the fact that the majority of children eventually enroll in a public day care center or school in the years following the intervention may be possible explanations for these results. In the second chapter, we investigate if the introduction of quotas in public universities affects employers’ perception of its students and graduates, regardless of their actual quota status. We explore the different timing of introduction of quota systems in two public universities in the State of Rio de Janeiro to estimate impacts of this policy on its students and graduates’ probabilities of being employed in the formal sector and hourly wages for those employed. Our results suggest that the introduction of quotas does not seem to have effects on the probability of being employed in the formal sector but there seems to be some negative effects on hourly wages for those who are employed in the formal sector for some of the cases considered. In the third chapter, we study the decrease in wage inequality among working age men in the Brazilian formal labor market from 1994 to 2016. We decompose inequality into its permanent and transitory components and find that the downward trend in wage inequality can be attributed to reductions in the transitory component from 1994 to 2005 (related to the economic stabilization process), and in the permanent component from 2010 to 2016. Our results also suggest that the permanent component has an important role in explaining wage inequality in Brazil, with age and education being accountable for a great share of permanent inequality.